(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article describes in detail the main tasks of teaching technology in general secondary educational institutions, improving the pedagogical mechanisms of teaching technology in primary schools based on the competency approach, and the main goal of teaching technology in general secondary educational institutions.